Model Pendampingan Manajemen Kaderisasi GP Ansor dalam Mencetak Da’i Muda Moderat dan Profesional di Kabupaten Nganjuk - Sukirno; Mastur; Supeno; Munahar (Ngaliman: Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service program aims to develop a mentoring model for the Ansor Youth Movement (GP Ansor) cadre management in producing moderate and professional young preachers in Nganjuk Regency. The activity was carried out in December 2025 at the NU Office in Nganjuk Regency using a participatory approach based on action research. The mentoring process included needs analysis, development of a young preacher cadre curriculum, training in moderate da'wah communication, and reflective evaluation with administrators and cadres. The results of the activity showed an increase in cadres' understanding of da'wah professionalism and religious moderation, the development of a structured cadre curriculum draft, and the formation of a young preacher development structure within the organization. This model contributes to strengthening individual capacity and sustainable institutional transformation of cadre development. Integrated managerial assistance has proven effective in encouraging the emergence of young da'i who are adaptive, inclusive, and have a national perspective.